1991
DOI: 10.1109/50.70005
|View full text |Cite
|
Sign up to set email alerts
|

Waveguide polarizer based on resonant tunneling

Abstract: We propose a novel and highly efficient waveguide polarizer based on the phenomenon of resonant tunneling. Based on this principle it is possible to fabricate both TE and TM pass polarizers. We show that by proper choice of materials it is possible to obtain TM mode loss greater than 80 dB/mm with a TE mode loss of only 0.5 dB/mm for the TE pass polarizer and TE mode loss up to 24 dB/mm with a TM mode loss less than 0.8 dB/mm for the TM pass polarizer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…is suitable only to obtain moderate polarization extinction ratio PER . Thyagaraw x jan et al 7 have proposed an integrated optic polarizer based on the resonant tunnelling effect which can also be designed to act either as a TE or a TM pass polarizer and have shown theoretically that with proper choice of materials one can obtain PER , 80 dB with an insertion loss for throughput polarisation as low as w x 0.5 dB. Using the same configuration Asakawa et al 8 have proposed a wavelength filter also.…”
Section: Introductionmentioning
confidence: 95%
“…is suitable only to obtain moderate polarization extinction ratio PER . Thyagaraw x jan et al 7 have proposed an integrated optic polarizer based on the resonant tunnelling effect which can also be designed to act either as a TE or a TM pass polarizer and have shown theoretically that with proper choice of materials one can obtain PER , 80 dB with an insertion loss for throughput polarisation as low as w x 0.5 dB. Using the same configuration Asakawa et al 8 have proposed a wavelength filter also.…”
Section: Introductionmentioning
confidence: 95%
“…Miliou et al reported a glass waveguide PBS based on stress-induced birefringence in an ionexchange waveguide [4]. Thyagarajan et al proposed PBSs based on resonant tunneling in three-core couplers [5]. These PBSs can be easily fabricated and are cost-effective, but long coupling length is required.…”
Section: Introductionmentioning
confidence: 98%
“…This large difference can be made use of in the construction of polarization selective devices based on resonant tunneling principle [7]. In the proposed configuration, the thin high-index medium (WG2) is so chosen that its TM mode is almost resonant with the TM mode of the outer identical guides.…”
Section: Principle Of Operationmentioning
confidence: 99%
“…The extinction ratios ER1 and ER3 are defined as Exit power of TM polarization in WG1 ER1 = 10log 10 ^ rTO __,__.__.__ ._ ",", In order to show the applicability of the concept of the resonant tunneling polarization splitter, we consider a glass waveguide structure with an intermediate silicon layer having the following values of the various parameters [11], [7]: ni = 1.527, n s = 1.5125, n 2 = 3.5 a = 2.0 /xm, d = 3.5 ^m and A = 1.3 /xm. (11) The individual isolated guides of the above structure support only TEo and TMo modes.…”
Section: = Pc~ Pmentioning
confidence: 99%
See 1 more Smart Citation